Bibliometric Mapping on Ethics, Privacy, and Trust in Digital Marketing - Puspitasari, Kiki Puput; Mujanah, Siti; Alif Fianto , Achmad Yanu (JEM17: Jurnal Ekonomi Manajemen, 2025)
The rapid advancement of digital technologies has significantly transformed modern marketing strategies, particularly in the utilization of consumer data, message personalization, and digital platform–based interactions. However, this evolution also raises complex ethical challenges related to privacy protection and the establishment of consumer trust. This study aims to map the development and research trends concerning ethics, privacy, and trust within the context of digital marketing through a bibliometric mapping approach. Data were collected from the Scopus database covering publications between 2013 and 2025 and analyzed using VOSviewer and Biblioshiny software. The analysis revealed four main research clusters: (1) ethics and social responsibility in digital marketing, (2) data privacy and information security, (3) consumer trust and loyalty, and (4) digital technology implementation in marketing strategies. The findings highlight that the success of digital marketing is not solely driven by technological innovation but also by how organizations uphold ethical principles and protect privacy to foster consumer trust. This study contributes to the growing body of digital marketing literature and offers practical insights for developing sustainable and integrity-oriented marketing strategies. Keywords: Bibliometric Mapping, Digital Marketing Ethics, Data Privacy, Consumer Trust, Online Marketing.